Thermal analysis for an experimental study of a cylindrical vertical solar chimney with internal PVC obstacles - Sakhri, Nasreddine; Menni, Younes; İnç, Mustafa; Ameur, Houari; Lorenzini, Giulio; Yu-Ming Chu (Oxford Univ Press, 2021)
Solar energy is the most renewable energy widely spread on the globe with several applications such as power generation and thermal comfort amelioration inside buildings. In the present study, one of the multiple solar energy techniques is discussed. New, simple and low-cost solar chimney (SC) made of polyvinyl chloride (PVC) tube with internal PVC obstacles was investigated experimentally. Heat transfer of air passing through the new device were studied and results show SC ability of increasing air temperature from 25 degrees C to 48 degrees C and reducing relative humidity from 40% to 10%. Internal PVC obstacles were responsible for increasing outlet air temperature by more than 7 degrees C in 63% of compared cases with simple PVC tube SC without internal obstacles. In the last part of the study, the new system was compared with three conventional square glazed SCs found in the literature. The new system outlet's air temperature was higher by 12 degrees C than the first two models and 2 degrees C with the third model, which increase the kinetic energy of air leaving the building and increase the internal airflow, ameliorating the air quality and reducing the age of air inside the dwellings. Obtained results encourage building designers and people to widely use SCs.
Keywords: experimental study; thermal analysis; solar chimney; PVC; obstacles; desert region